Supra-glacial deposition and flux of catastrophic rock-slope failure debris, south-central Alaska - Uhlmann, Manuela; Korup, Oliver (Prof.); Huggel, Christian; Fischer, Luzia; Kargel, Jeffrey S. (Earth Surface Processes and Landforms, 2013)
The ongoing debate over the effects of global environmental change on Earth's cryosphere calls for detailed knowledge about process rates and their variability in cold environments. In this context, appraisals of the coupling between glacier dynamics and para-glacial erosion rates in tectonically active mountains remain rare. We contribute to filling this knowledge gap and present an unprecedented regional-scale inventory of supra-glacial sediment flux and hillslope erosion rates inferred from an analysis of 123 large (> 0 center dot 1km2) catastrophic bedrock landslides that fell onto glaciers in the Chugach Mountains, Alaska, as documented by satellite images obtained between 1972 to 2008. Assuming these supra-glacial landslide deposits to be passive strain markers we infer minimum decadal-scale sediment yields of 190 to 7400tkm-2yr-1 for a given glacier-surface cross-section impacted by episodic rock-slope failure. These rates compare to reported fluvial sediment yields in many mountain rivers, but are an order of magnitude below the extreme sediment yields measured at the snouts of Alaskan glaciers, indicating that the bulk of debris discharged derives from en-glacial, sub-glacial or ice-proximal sources. We estimate an average minimum para-glacial erosion rate by large, episodic rock-slope failures at 0 center dot 5-0 center dot 7mmyr-1 in the Chugach Mountains over a 50-yr period, with earthquakes likely being responsible for up to 73% of this rate. Though ranking amongst the highest decadal landslide erosion rates for this size of study area worldwide, our inferred rates of hillslope erosion in the Chugach Mountains remain an order of magnitude below the pace of extremely rapid glacial sediment export and glacio-isostatic surface uplift previously reported from the region.